Mutations and a polymorphism in the factor VIII gene discovered by denaturing gradient gel electrophoresis. - Kogan, S (1990)
Hemophilia A results from mutations in the gene coding for coagulation factor VIII. We used denaturing gradient gel electrophoresis to screen for mutations in the region of the factor VIII gene coding for the first acidic domain. Amplification primers were designed employing the MELTMAP computer program to optimize the ability to detect mutations. Screening of amplified DNA from 228 unselected hemophilia A patients revealed two mutations and one polymorphism. Rescreening the same population by making heteroduplexes between amplified patient and control samples prior to electrophoresis revealed one additional mutation. The mutations include two missense and one 4-base-pair deletion, and each mutation was found in patients with severe hemophilia. The polymorphism, located adjacent to the adenine branch site in intron 7, is useful for genetic prediction in some cases where the Bcl I and Xba I polymorphisms are uninformative. These results suggest that DNA amplification and denaturing gradient gel electrophoresis should be an excellent strategy for identifying mutations and polymorphisms in defined regions of the factor VIII gene and other large genes.